1992
DOI: 10.1111/j.1365-3180.1992.tb01861.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of root and shoot competition between spring cereals and Avena fatua L.

Abstract: Summary: Résumé: Zusammenfassung Two cultivars of each of three spring cereals (wheat, barley and oats) were grown with Avena fatua in a box experiment, where the effects of root and shoot competition were separated using soil and aerial partitions. Measures of resource complementarity (RYT) and of the relative severity of competition indicated that competition for soil resources, particularly nitrogen, was more severe than competition for aerial resources, i.e. light. When both root and shoot competition occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
2
13

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 21 publications
(17 reference statements)
8
78
2
13
Order By: Relevance
“…In a study with 20 winter wheat varieties, most that were 83 cm or taller were classified as good competitors, but two of the shortest varieties were also among the best in competing with weeds . Similarly, in a study with different varieties of wheat, barley and oat, there was little evidence that differences in shoot competitive ability were due to differences in plant height (Satorre and Snaydon 1992).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study with 20 winter wheat varieties, most that were 83 cm or taller were classified as good competitors, but two of the shortest varieties were also among the best in competing with weeds . Similarly, in a study with different varieties of wheat, barley and oat, there was little evidence that differences in shoot competitive ability were due to differences in plant height (Satorre and Snaydon 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Differences among varieties within species were also identified in some crops but the differences were strongly influenced by seasonal conditions. In another study, oats and barley were found to be generally more competitive than wheat, but there were significant differences in competitiveness among varieties of the three cereals (Satorre and Snaydon 1992).…”
Section: Mots Clés: Blé Roux Vitreux De Printemps (Brvp) Blé De Prinmentioning
confidence: 99%
“…Segundo Garrity et al (1992), a estatura de planta em arroz associa-se estreitamente com a supressão de plantas daninhas; contudo, pode não ser a única característica que se relaciona, pois mesmo em cultivares de porte alto foram observadas diferenças para massa seca de plantas daninhas. Já Satorre & Snaydon (1992) relataram existir pouca importância da estatura em definir a capacidade competitiva de cereais com plantas daninhas. Adicionalmente, Balbinot Jr. et al (2003), em experimento com oito cultivares de arroz que apresentavam variação de ciclo, não encontraram associação entre ciclo e estatura de planta.…”
Section: Resultsunclassified
“…In many studies, plant height has been shown to be a significant or even the only factor for cereal competitiveness [10,29,30]. In contrast, other researchers have indicated that plant height is of minor importance [31,32]. In a study by O'Donovan et al [15], differences in seedling establishment of wheat and barley varieties tended to influence competitive ability against wild oat (Avena fatua L.) more than did plant height.…”
Section: Discussionmentioning
confidence: 99%